Psychiatric disorders in women and men up to five years after undergoing assisted reproductive technology treatment – a prospective cohort study. (2nd October 2019) - Volgsten, Helena; Schmidt, Lone; Skoog Svanberg, Agneta; Ekselius, Lisa; Sundström Poromaa, Inger
Abstract: This is a prospective cohort study with the objective to describe psychiatric disorders, such as any mood and anxiety disorders, in both women and men five years after assisted reproductive technology (ART). The Primary Care Evaluation of Mental Disorders (PRIME-MD) questionnaire, based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), was used as the diagnostic tool to evaluate psychiatric disorders. Logistic regression analysis was used to calculate odds ratios (ORs) and confidence interval (CI) for factors associated with psychiatric disorders at the follow-up. Overall, 278 (63.3%) women and 183 (41.7%) men filled in and returned the questionnaire. Approximately 11.5% of women and 5.5% of men fulfilled the criteria for any psychiatric diagnosis. Of these, any mood disorder was present in 9.4% of women and 4.4% of men. The major risk factor for mood or anxiety disorders at follow-up was mood or anxiety disorders at the time of the index ART. Mood disorders were not more common in women who remained childless after ART. In conclusion, these findings indicate that psychiatric disorders at five years follow-up after ART are less common than at the baseline assessment in conjunction with the ART.